TPACK Research Trends in Indonesia: Contributions to Enhancing the Equivalency Education History Teacher Community - Sutimin, Leo Agung; Sariyatun, Sariyatun; Musadad, Akhmad Arif; Yuniyanto, Tri; Abidin, Nur Fatah (Journal of Nonformal Education, 2025)
Background: Technological Pedagogical Content Knowledge (TPACK) is a vital framework for integrating technology into education. In Indonesia, TPACK research has grown significantly, yet most studies focus on science and mathematics, leaving gaps in social studies, particularly history education. Additionally, its potential in supporting the equivalency education system, which serves non-formal learners, remains underexplored. Research Objectives: This study aims to analyze TPACK research trends in Indonesia (2019–2023), examine its contribution to the equivalency education history teacher community, and provide recommendations for integrating TPACK into history education. Research Method: Using bibliometric analysis, this study analyzed 1,208 documents from the Scopus database with the keyword "TPACK." The analysis focused on publication trends, dominant themes, and geographical contributions, particularly in history education and equivalency education. Research Findings: Indonesian researchers dominated TPACK research during the study period. Most studies focused on pre-service teacher training and learning media development, primarily in science and mathematics. Limited attention was given to social studies, especially history, highlighting an opportunity to expand TPACK research into history education and the equivalency education system. Research Conclusion: This study emphasizes the need to integrate TPACK into history education to enhance the competencies of equivalency education history teachers. By leveraging TPACK, educators can create innovative, technology-enhanced learning experiences tailored to non-formal learners. Professional development programs are also essential to equip teachers with TPACK skills. Research Novelty: This study provides a comprehensive bibliometric analysis of TPACK trends in Indonesia, identifies gaps in social studies research, and offers practical recommendations for applying TPACK in history education and non-formal learning contexts. It paves the way for future research and practical applications in underserved educational areas.